2016
DOI: 10.7868/s0026898416050104
|View full text |Cite
|
Sign up to set email alerts
|

Новые Гены МикроРНК, Гиперметилированные При Раке Молочной Железы

Abstract: MicroRNAs play an important role in the regulation of expression of many genes involved in cancer pathogenesis. One of the causes of miRNA level deregulation in tumors is the methylation of CpG islands in the promoter regions of the genes that encode them. Hypermethylation may lead to the suppression of miRNA gene expression and, as a consequence, to a decrease in their inhibitory effect on target gene mRNAs. A search for new miRNA genes hypermethylated in breast cancer has been carried out in the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
6
0
5
Order By: Relevance
“…Recent studies have shown that Snail and ZEB1 can also reduce cell adhesion, increase cell migratory capacity 7678 , and promote apoptosis 79,80 . These phenotypic features have also been observed during FECD pathogenesis 8183 .…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have shown that Snail and ZEB1 can also reduce cell adhesion, increase cell migratory capacity 7678 , and promote apoptosis 79,80 . These phenotypic features have also been observed during FECD pathogenesis 8183 .…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have shown that Snail and ZEB1 can also reduce cell adhesion, increase cell migratory capacity [7476], and promote apoptosis [77, 78]. These phenotypic features have also been observed during FECD pathogenesis [7981].…”
Section: Discussionmentioning
confidence: 99%
“…The promoter CpG islands of miR-130b was not methylated in NSCLC [ 40 ]. However, it had an increased methylation frequency in breast cancer [ 41 ]. The promoter of miR-130b~301b cluster was significantly hepermethylated in prostate cancer tissues compared with morphologically normal ones, which impaired cellular senescence and fuel malignant transformation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%